If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 3) = 2x + 66 Reorder the terms: 8(3 + x) = 2x + 66 (3 * 8 + x * 8) = 2x + 66 (24 + 8x) = 2x + 66 Reorder the terms: 24 + 8x = 66 + 2x Solving 24 + 8x = 66 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 24 + 8x + -2x = 66 + 2x + -2x Combine like terms: 8x + -2x = 6x 24 + 6x = 66 + 2x + -2x Combine like terms: 2x + -2x = 0 24 + 6x = 66 + 0 24 + 6x = 66 Add '-24' to each side of the equation. 24 + -24 + 6x = 66 + -24 Combine like terms: 24 + -24 = 0 0 + 6x = 66 + -24 6x = 66 + -24 Combine like terms: 66 + -24 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| x+1=10-8 | | 10z+4=54 | | 2+10x=-7x | | 6x+15=7x+13 | | w=67-21 | | 10+x=11+x | | 4=r^2/3 | | 2v-56=34 | | 12+4(w-5)=16-2w | | 7-7x-4=-71+5x-10 | | n+50=110 | | 2.2x+63=3.7x+18 | | 4c-13=23 | | n+42=123 | | -4y=-12x+32 | | 42+n=123 | | 0.6x+1.9=0.9x-0.2 | | X^2+y^2+4x-20y+95=0 | | 7y-8=4+12y | | 49=12y-1 | | 6x+5=-4+2x+17 | | log(3x-3)=log(x+1)+log(4) | | y-1.6=9 | | (2x+3)-(y+3)= | | 4x-(0.56x-1.33)= | | 5=-3x-29 | | 31=a-57 | | 11x-6-6x=6x-4 | | 4-7sinex=0 | | t-8=26 | | z+16=17 | | 4-7sinx=0 |